ENHANCING LISTENING SKILL BASED ON AUTHENTIC MATERIALS IN HIGHER EDUCATION - Erna Nur Kholida (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
The objectives of this study was to know the using of YouTube materials in learning listening skills of university students and to assess students’ attitude towards the using of it. The sample of the student population for this study was 61 students. The t-test was used to compare the listening competency of the experimental group. The one-group pretest-posttest design was implemented in this study. The instruments used in this study were 1) lesson plans 2) listening comprehension tests (pretest and posttest) and 3) a questionnaire of the students’ attitude. Regarding the data analysis, mean and t- test scores for the dependent sample were employed. The T-Test scores was 37.59 and mean of pre-test was 50.80 while mean of post test was 84.91. The result indicated that 1) the students’ English listening comprehension ability increased significantly after learning with YouTube material and 2) students had positive attitude towards using videos in learning listening skills. Keywords: Authentic material, Listening, Higher Education AbstractTujuan dari penelitian ini adalah untuk mengetahui penggunaan materi YouTube pada ketrampilan menyimak pada mahasiswa dan untuk mengetahui sikap dari mahasiswa dalam penggunaannya. Sample dan populasi dari penelitian ini berjumlah 61 orang. Uji t digunakan untuk membandingkan kemampuan listening pada kelas eksperiment. Grup pre-test-post-test digunakan dalam penelitian ini. Instrumen yang digunakan adalah 1) rencana pembelajaran 2) tes listening (post-test dan post-test) dan 3) kuesioner sikap. Hasil uji t-test adalah 37.59 dan mean pre-test adalah 50.80 sedangkan mean dari post-test adalah 84.91. Melihat analisa data, mean, dan hasil t-test menunjukkan hasil 1) kemampuan mendengarkan bahasa Inggris meningkat secara siknifikan setelah menggunakan materi Youtube dan 2) mahasiswa memiliki sikap yang positif dalam pembelajaran ketrampilan menyimak. Kata Kunci: Authentic material, Listening, Higher Education